The FRAILMar Study Protocol: Frailty in Patients With Advanced Chronic Kidney Disease Awaiting Kidney Transplantation. A Randomized Clinical Trial of Multimodal Prehabilitation - Pérez-Sáez, María José; Morgado-Pérez, Andrea; Faura, Anna; Muñoz-Redondo, Elena; Gárriz, Miguel; Muns, Maria Dolors; Nogués, Xavier; Marco, Ester; Pascual, Julio (Frontiers in Medicine, 2021)
Introduction: Frailty is very frequent among patients with chronic kidney disease (CKD) who are awaiting deceased donor kidney transplantation (KT), and transplant outcomes are worsened in those frail recipients. Frailty and poor fitness powerfully predict mortality, kidney graft survival, and healthcare utilization after KT. Intervention is essential to improve survival and quality of life for frail CKD patients, regardless of their age. Studies of post-transplant physical therapy intervention have been met with limited success, in large part due to high dropout rates. A pre-transplant clinical framework for multimodal prehabilitation interventions including physical therapy, nutritional measures, and psychological support scheduled during the KT waiting list period may improve patient retention and compliance, better mitigate the effects of frailty and poor fitness after KT, and improve main outcomes in frail CKD patients. Main objective: To study the effectiveness, feasibility, and safety of multimodal prehabilitation (exercise, nutritional plans, psychological advice) in KT candidates. Methods: Randomized controlled clinical trial in 38 frail and 76 non-frail KT candidates. The prehabilitation program will consist of physical exercise (24 sessions, 8 weeks), nutritional supplementation, and psychological advice. The primary endpoint will be a composite achievement of clinical and functional main outcomes in frail and non-frail KT candidates at 90 days post-transplantation. Secondary outcomes include changes in exercise capacity, physical activity, gait speed, respiratory and peripheral muscle strength, muscle size, body composition, performance in activities of daily living (basic and instrumental), anxiety and depression symptoms, and health-related quality of life. Feasibility of the intervention will be also analysed. Expected results: Multimodal prehabilitation is a feasible and effective intervention to decrease bad outcomes at 90 days post-KT of 25% and 12.5% in frail and non-frail patients, respectively. Trial registration: clinicaltrials.gov (NCT04701398).